Energy Assessment of Hazelnut Shells (Corylus avellana L.) of Selected Turkish Varieties - Kamila E. Klimek; Saban Kordali; Anna Borkowska; Ferah Yilmaz; Grzegorz Maj (Energies, 2025)
The purpose of this study was to evaluate the energy and environmental potential of waste biomass in the form of hazelnut shells from selected Turkish varieties of Corylus avellana L. Eight commercial varieties (Çakıldak, Foşa, İnce Kara, Kalın Kara, Palaz, Tombul, Yassı Badem and Yuvarlak Badem) grown in different regions of the Black Sea coast of Turkey were analyzed. The scope of this study included whole nut and shell weight determination, technical and elemental analysis, higher heating value (HHV) and lower net heating value (LHV), as well as emission factors (CO, CO2, NOx, SO2, dust) and flue gas composition based on stoichiometric calculations. The results showed a significant effect of varietal characteristics on all analyzed parameters. The share of shell in the total weight of the nut ranged from 43.5% (Tombul) to 55.3% (İnce Kara). HHV values ranged from 18.37 to 19.20 MJ·kg−1, and LHV from 17.05 to 17.90 MJ·kg−1. The İnce Kara and Yassı Badem varieties showed the most favorable energy properties. Elemental analysis confirmed a low nitrogen and sulfur content, which translated into low NOx and SO2 emissions. NOx emissions were lowest for the Tombul variety (1.43 kg·Mg−1), and SO2 emissions were close to zero in each variety. The results confirm that Turkish hazelnut shells are a valuable energy resource and can be used as solid fuel or supplementary biomass. In particular, the İnce Kara variety was identified as the most promising due to its high shell weight, very good fuel properties, and high yield potential. This study underscores the importance of selecting the right variety to optimize agricultural waste utilization strategies within a circular economy.